Strategi Pengembangan Digitalisasi Desa Wisata : Studi Kasus Desa Jatiluwuh, Kabupaten Tabanan Provinsi Bali - Kharisma, Bayu (Jurnal Ilmiah Cakrawarti, 2023)
The existence of tourist villages today is inseparable from Information and Communication Technology (ICT) and digital media. Jatiluwih Village is one of the villages located in Tabanan Regency, Bali Province, which currently has social media and a website, but their use could be more optimal. The problem raised in this study is that the digitalization of tourism in the village has yet to be optimal. Thus, the purpose of this study was to determine the strengths, weaknesses, opportunities, and threats of developing tourism digitalization in Jatiluwih Village, Tabanan Regency, Bali Province, knowing community involvement in developing tourism digitization in Jatiluwih Village and developing strategies for involving community participation in developing tourism digitalization in Jatiluwih village. The research methods used are gap analysis, swot analysis, and litmus test. The results of the study show that Jatiluwih Village has opportunities, namely cooperation with external parties for village development, there is a budget allocation from the central government to develop a tourism village (Village Fund), tourists who visit the Tourism Village, the opportunity to promote the village to a broader network, and tourist villages have natural resources for tourism attractions. However, several threats must be considered; namely, technology reduces community interaction, technology increases social disparities (some people do not benefit from the use of technology), stopping funding from the Central Government affects the management of tourist villages and the COVID-19 pandemic and policy Enforcement of Community Activity Restrictions (PPKM).